Answer:
Step-by-step explanation:
(2n - 3)(5n + 6) = 2n*(5n + 6) -3*(5n +6)
=2n*5n + 2n*6 -3*5n + (-3)*6
=10n² + 12n - 15n - 18
= 10n² -3n - 18
If you want x, rearrange <span>Z=y+mx as follows: mx = z - y. Then div. all 3 terms by m:
z-y
x = ------- (answer).
m </span>
By evaluating the linear equation, we can complete the table:
x: -2 | -1 | 0 | 1 | 2 |
y: -3 | -1 | 1 | 3 | 5 |
<h3>
How to complete the given table?</h3>
Here we want to complete the table:
x: -2 | -1 | 0 | 1 | 2 |
y: | | | | |
To get the correspondent values in the "y" row, you just need to evaluate the linear function in the given values of x.
Here the function is:
f(x) = 2x - 1
Evaluating it we get:
f(-2) = 2*(-2) + 1 = -3
f(-1) = 2*(-1) + 1 = -1
f(0) = 2*0 + 1 = 1
f(1) = 2*1 + 1 = 3
f(2) = 2*2 + 1 = 5
Now we just put these values in their correspondent place on the table.
x: -2 | -1 | 0 | 1 | 2 |
y: -3 | -1 | 1 | 3 | 5 |
If you want to learn more about linear functions:
brainly.com/question/1884491
#SPJ1
Answer:
600
Step-by-step explanation:
anything times 1 is itself
Answer:
A, ![\sqrt{17}](https://tex.z-dn.net/?f=%5Csqrt%7B17%7D)
Step-by-step explanation:
a^2 + b^2 = c^2
8^2 + b^2 = 9^2
64 + b^2 = 81
b^2 = 17
b = ![\sqrt{17}](https://tex.z-dn.net/?f=%5Csqrt%7B17%7D)